Neuroimmune Activation in Chronic Heart Failure - Fiore, Giorgio; Suppress, Patrizia; Triggiani, Vincenzo; Resta, Francesco; Sabba, Carlo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2013)
Cardiac hypertrophy/remodeling manifests as a critical condition which may likely predispose to the risk of fatal heart failure and multiple organ dysfunction if not efficiently addressed, as a result of irreversible neuroendocrine, autonomic and immune system imbalances. Undeniably, the over-excitation of sympathetic and/or the breakdown of central parasympathetic tone play a significant role to be the basis of the persistent immune activation in chronic heart failure (CHF) which, to a certain extent, is primed by inflammatory reactions in the Central Nervous System. Moreover, till today, the clinical management of CHF seeks the identification of molecularly targeted drugs in comparison to those considered so far. This review focuses on the possible neuroimmune-mediated pathways involved in CHF and throws light on the current therapeutic strategies.
Keywords: Autonomic system